Integrasi Olahraga dalam Kegiatan Bakti Sosial di Kelurahan Mabar Hilir, Kota Medan - Penata Manik; Praninci Praninci; Parlindungan Nababan; Pras Dio Nanda; Aszon Fisi Lahagu; Novita Putri Yani Ndruru; Yunita Mandasari; Anugrah Panca Dinata; Trifosa Angelina Sembiring; Muhammad Ridho Maulana; Ody Pratama Elmahdi; Nurfadillah Siregar; Nopi Hardiyanto; Nuraini Nuraini; M. Syahputra (INSPIRETECH GLOBAL INSIGHT & (ISORI KAMPAR), 2024)
Objectives: This community service aimed to implement an integrated sports approach within social service activities in Mabar Hilir Sub-district, Medan City. Methods: The program addressed the interrelated issues of low physical activity, limited social interaction, and minimal health awareness among residents. Using a participatory approach, this initiative combined sports activities with health education and community development. Results: The six-month program involved 235 participants across different age groups and demonstrated significant improvements in health awareness (37% increase), regular physical activity participation (42% increase), and community cohesion (65% of participants reported stronger social bonds). Implementation challenges included initial participation hesitancy, infrastructure limitations, and scheduling conflicts, which were addressed through adaptive strategies. Conclusion: The successful integration of sports into social services provides a replicable model for holistic community development in similar urban settings.